Integral Health Brigades. An Experience in Cienfuegos after Hurricane Denis - Víctor René Navarro Machado; William Alfonso Delgado; Salvador Tamayo Muñiz; Carlos Castro Cabanes; Roberto Baños García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: Hurricane Denis (July 2005) affected Cienfuegos province, causing great economic lost, no life was lost though. Health sector put in practice the previewed plans, including the levelled unfolding of 11 Integral Health Brigades up to the most affected places since the beginnings of the recovering phase. Objectives: to analyze the impact of the Integral Health Brigades in the affected areas. Method: For the article it were revised the statistics, enquiries to the population and workers of the health sector carried out by each Brigade, as well as the conclusions of the experience, analyzed in a provincial meeting for this purpose. Results: There was no disease outbreak, not even changes in morbidity. The psychological affection was very little. Population expressed its satisfaction for the immediate attention offered by health system. It allowed the direct work with people of greatest vulnerability and the stratification of their management in a more integral way. The labour bettered communitarian education and health promotion. Conclusions: in the most affected areas it was a necessary and positive element to elevate integral health attention to the community as part of the support to the civil defence sector.